2016
DOI: 10.1152/japplphysiol.00662.2015
|View full text |Cite
|
Sign up to set email alerts
|

No reserve in isokinetic cycling power at intolerance during ramp incremental exercise in endurance-trained men

Abstract: During whole body exercise in health, maximal oxygen uptake (V̇o2max) is typically attained at or immediately before the limit of tolerance (LoT). At the V̇o2max and LoT of incremental exercise, a fundamental, but unresolved, question is whether maximal evocable power can be increased above the task requirement, i.e., whether there is a "power reserve" at the LoT. Using an instantaneous switch from cadence-independent (hyperbolic) to isokinetic cycle ergometry, we determined maximal evocable power at the limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…3). This finding is unique because previous work has reported either the presence (25,26) or absence (11,17) of a power reserve at the LoT. The difference in findings among publications may lie in the interpretation of ⌬P at the LoT.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…3). This finding is unique because previous work has reported either the presence (25,26) or absence (11,17) of a power reserve at the LoT. The difference in findings among publications may lie in the interpretation of ⌬P at the LoT.…”
Section: Discussionmentioning
confidence: 62%
“…During RI exercise, the LoT and an inability to continue exercise have been attributed to an inability of muscle to meet the torque or power requirements of the task, despite maximal effort by the participant (11,17). It has been reported that at the LoT following an exhaustive RI exercise test, some individuals still are capable of volitionally producing power far greater than the PO associated with the termination of the RI test (i.e., evidence of a power reserve), whereas others are unable to voluntarily generate additional power beyond that required of the RI PO peak (i.e., no power reserve).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maximal RPE was not reported so it is difficult to interpret these findings; however, it is plausible that other factors help explain the mechanistic basis for the effects of verbal encouragement on exercise tolerance and that these mechanisms are different for trained versus untrained individuals. Other potential mechanisms include improvements in affect (Hall et al, 2002) and alterations in motor unit activation (Ferguson et al, 2016).…”
Section: Psychological Basismentioning
confidence: 99%